Peran Konselor dalam Menghadapi Perilaku Temper Tantrum - Ari Setyawan, David (IAIN Kudus, 2019)
THE ROLE OF COUNSELOR IN DEALING WITH TEMPER TANTRUM BEHAVIOR. Children aged 4-7 years is a time to get acquainted and learn to deal with disappointment when their desire cannot be fulfilled. Disappointment, anger, sadness, and so on is a natural feeling. However, often, parents unwittingly 'clog up' the emotions felt by the children. For example, when a child cries out in disappointment, parents in various ways try to entertain, distract, scold, and so on in order to stop the child's crying. This actually makes the children's emotions do not come out freely. If this continues, the result will be what is called the emotional pile. This pile of emotions can later explode out of control and appear as temper tantrum. Bursting anger with dangerous actions and causing injury is one form of tantrum so that children get what they want. The realization of the children’s tantrum that can pose a risk of injury can be either dropping to the floor, hitting the head, or throwing things. These are considered as the first stage of temper tantrum when the children are able to express their frustration. If temper tantrums have already appeared in the form of harmful behaviors and have the potential to cause damage, then intervention must be done immediately. The bigger the child, the more powerful the energy is and the more difficult it will be for parents to control or prevent uncontrolled behavior.Keywords: The role of counselor, Temper Tantrum.